Oxydative stress in rats caused by coal dust plus cigarette smoke - Kania, Nia; Setiawan, Bambang; Kusuma, H.M.S. Chandra (Universa Medicina, 2011)
Coal dust and cigarette smoke are pollutants found in coal mines that are capable of inducing oxidative stress, the effects of which on blood malondialdehyde (MDA) level and serum superoxide dismutase (SOD) level are still unknown. The purpose of the present study was to evaluate the effect of coal dust and cigarette smoke on levels of MDA and SOD in rats. An experimental study was done on Wistar male rats divided into the following groups: control (C), coal dust exposure (14 days) (CDE), cigarette smoke exposure (14 days) (CSE), coal dust exposure (7 days) followed by cigarette smoke exposure (7 days) (CDE+CSE), cigarette smoke exposure (7 days) followed by coal dust exposure (7 days) (CSE+CDE). All exposures increased MDA levels and decreased SOD activity significantly between groups (p=0.000). All exposure groups had significantly increased blood MDA levels, compared to the control group, although there was no difference between CSE + CDE and CDE + CSE. For SOD levels, all exposure groups had significantly decreased the SOD levels compared to control. But there were no significant differences between CSE vs CDE and CDE + CSE vs CSE + CDE. We conclude that exposure to cigarette smoke significantly increases blood MDA level and decreases serum SOD activity, which was not found in exposure to coal dust. Combined exposures also increase blood MDA level and decrease serum SOD activity significantly.